School Entry Age Policy and Adolescent Risk–Taking - Cristina Lopez-Mayan; Giulia Montresor; Catia Nicodemo (Institute of Labor Economics (IZA), 2024)
This paper investigates the impact of the school entry age policy on adolescent risk–taking behaviors. The policy mandates that children begin primary education in the year they turn six, creating relative age differences within cohorts due to a January 1st cutoff date. Using data from the Spanish School Survey on Drug Use, we analyze a comprehensive set of risky behaviors, including substance use, gambling, gaming, internet use, and sexual activity among students in the early adolescence in compulsory education. Employing an empirical strategy that compares students born in December (young–for–grade) and January (old–for–grade) while controlling for potential confounders, we find that young–for–grade students are less likely to engage in risky behaviors. Findings are consistent across various robustness checks. Further analysis shows that age differences and educational cycle effects contribute to the findings, with gender-specific patterns for boys and girls, while school type shows limited variation. Most behavioral differences diminish by late adolescence in high school. This research expands our understanding of the non-academic impacts of school entry age policies on education and adolescent development.
Keywords: I12; I21; J13; 330; young–for–grade and old–for–grade students; school entry age; risky health behaviors; education policy